A Analisis Nilai Tambah Limbah Padat Kelapa Sawit Di Provinsi Jambi - HARKENI, ASTI HARKENI; Ramadhan Hudsi, Rafi; Andina Putri, Rizqy; Syaputra, M. Rialdi (Brida Provinsi Jambi, 2025)
The extensive oil palm plantations in Jambi Province have the potential to generate significant waste, impacting the environment. One hectare of oil palm plantation yields approximately 10 tons of fronds and 75 tons of trunks. Furthermore, for every 1 kg of palm oil produced, 4 kg of dry biomass is generated. However, this palm waste also holds potential for providing economic value-added for farmers and fostering the growth of new MSMEs (Micro, Small, and Medium Enterprises). This research aims to identify the value-added generated from utilizing community-owned oil palm solid waste by transforming it into valuable products for the people of Jambi Province. The study employed a mixed-methods approach, combining qualitative and quantitative research. Data was collected through Focus Group Discussions (FGDs) and direct interviews with MSMEs and community-based oil palm waste processing groups. The value-added from the waste was then calculated using the Hayami value-added method. The results indicate that processing waste fronds into compost yields the highest value-added compared to processing midribs into woven products or trunks into palm sugar. The value-added for compost fertilizer per 1 kg of oil palm fronds is IDR 12,403.32. Consequently, the profit margin received by the Village-Owned Enterprise (BUMDesa) or the entrepreneur is 86.3%.